PENGARUH PEMBERIAN TEKNIK RELAKSASI AUTOGENIK TERHADAP PENURUNAN TINGKAT NYERI PADA PASIEN POST OPERASI APPENDIKTOMI - Fadli Syamsuddin; Dewi Modjo (-, 2021)
Influence giving relaxation techniques  level of post operative paint in patients appendiktomy surgical hospital Prof. DR. Aloei Saboe Gorontalo City. Appendicitis is a disease of major surgery most often appendicit is can occuratany age, butis most common in early adulthood. High mortality rateof this disease befor eage. Appendicitis can also betermed as appendicitis, when the inflammation gets worseand become infected, The Handlingappendicitisissurgery, complaintsand symptoms that often the surgical wound pain is often treated with farmakolocy anestheti analgesic drugs to suppress pain. Purposeof this study was to determine the effect of autogenic relaxation techniques to decrease the level of pain in patients with post surgical hospitals appendiktomy. Prof. DR. H. Aloei Saboe Gorontalo city.The study design use dispre experimental research design one group pre-test-post-test is to test without a control group. Population and sample are all post operative patients in hospitals Aloei Saboe numbered. Appendiktomy patients with 30 patient samples. Sampling technique withconsecutive sampling.The analysis was conducted in stages (1) to save a univariate analysis of frequency distribution, (2) statistical test that an alyzes bivariat paired T test, in order to variable research with significance level p<0.05. Statistite stusing paired T test p value<0.001, by p<0.05 then there wast he effect of autogenic relaxation techniques to decrease the level of post operative pain in patients appendiktomy surgical hospitals. Prof. Dr. Aloei Saboe Gorontalo city.